العنف والمسكوت عنه في رواية " أصابع لوليتا " لواسيني الأعرج - أحمد بوغرارة; وقاد مسعود (University of Eloued جامعة الوادي, 2025)
حظي المسكوت عنه بأهميّة بالغة في الدّراسات النّقدية العربيّة والمعاصرة ، ونجد بأنّ النّص الرّوائي يضطر في الغالب إلى السكوت ، ويترك فراغات و فجوات، وذلك لوقوعه تحت حصار القيود، وسلطات قامعة كالدولة والإرهاب، وتحت سلطات الدّين والجنس والأعراف والتقاليد، و التي تتطلب جهدا وطاقة فاعلة من قبل القارئ لفك شفراتها وتأويلها. و يعدّ الروائي الجزائري " واسيني الأعرج " واحدا من الروائيين الذين اتخذوا المسكوت عنه كفضاء رمزي لتمرير رسائل معينّة خاصّة المقموع السيّاسي الذي يهيمن على نصوصه الروائية ويعود في رواية " أصابع لوليتا " لواسيني الأعرج ليشتغل على موضوعة السيّاسة التي اتخذها الروائي محورا لمعظم أعماله الأدبيّة، والتي ارتبطت بتناولها من منظور جديد حيث تميّزت بامتلاكه حرية لمواجهة القضايا السيّاسية بجرأة فائقة، ويحاول الأعرج الحفر في تاريخ السّلطة ليكشف الجانب المظلم فيها، و يصيغ الموقف النقدي المعارض لها من خلال إحالته إلى مواضعَ العنف السّياسي، فكيف اشتغل " واسيني الأعرج"* على المقموع السيّاسي في الرّواية ؟ و هل عالجه من منظور فنّي جمالي؟. Summary The unspoken has gained great importance in Arab and contemporary critical studies. We find that the novel text is often forced to remain silent, leaving gaps and gaps, due to its being under the siege of restrictions and oppressive authorities such as the state and terrorism, and under the authorities of religion, gender, customs and traditions, which require effort and effective energy from the reader to decipher and interpret them. The Algerian novelist "Wasini Al-Araj" is one of the novelists who took the unspoken as a symbolic space to pass on certain messages, especially the political oppressor who dominates his novelistic texts. In the novel "Lolita's Fingers" by Wasini Al-Araj, he returns to work on the subject of politics, which the novelist took as the focus of most of his literary works, which were linked to dealing with it from a new perspective, as it was distinguished by his freedom to confront political issues with great boldness. Al-Araj tries to dig into the history of power to reveal the dark side of it He formulates the critical position opposing it by referring it to places of political violence, so how did Wasini Al-Araj* work on the political oppression in the novel? Did he treat it from an artistic and aesthetic perspective? Keywords: the unspoken, Lolita's fingers, Wassini Al-Araj, violence, critical opposition, aesthetic perspective.
مقال . القارئ للدراسات الأدبية و النقدية و اللغوية. مج 08. ع 02
Keywords: المسكوت عنه؛ أصابع لوليتا؛ العنف ؛ واسيني الأعرج؛ النقدي المعارض؛ المنظور الجمالي